Analisis Efektivitas Program Bantuan Langsung Tunai Ditinjau Dari Perspektif Mahasiswa Fakultas Hukum Universitas Pembangunan Nasional “Veteran” Jakarta - Fazl Mawla Febrian; Novita Fitria Azzahra; Farchanza Haykanna Pireno; Satino Satino (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
"Indonesia Golden 2045" is a big vision with the goal of making Indonesia a developed country by 2045, on the other hand poverty is still a serious problem facing Indonesian society. The government has launched a number of social assistance programmes to reduce the poverty rate and improve the well-being of the population. Despite this, the effectiveness of these programmes is still a matter of debate among several parties. In this context, research into student perspectives on the effectiveness of government programmes in particular Cash Direct Assistance (BLT) in poverty alleviation efforts becomes relevant and important. In order to obtain real comparisons as well as actual information relating to the existence of government social assistance programmes, the data collection system on this study uses an online survey in the form of a questionnaire containing questions about the perspective related to the problems of the BLT program with students of the Faculty of Law of the National University of Development “Veteran” Jakarta (UPNVJ) as the target respondents continued with a review of data from previous sources. The research is expected to provide a more comprehensive understanding of the extent to which government social assistance programmes benefit communities and any obstacles they encounter in their implementation.